The influence of the soaking temperature rotary forging and solution heat treatment on the structural and mechanical behavior in ni-rich niti alloy - Rodrigues, Patrícia Freitas (2022)
PTDC/CTM-CTM/29101/2017?POCI-01-0145-FEDER-029101 UIDB/50025/2020-2023 APQ-1 2009/02 E-26/110.414/2010 APQ-1 2011-2 E-26/110.269.2012 E-26/111.435/2012 11943-13-0 307798/2015-1